2020
DOI: 10.1016/j.clinph.2020.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular involvement in COVID-19 critically ill patients

Abstract: Highlights Many COVID-19 patients require ICU stay which can result in neuromuscular damage. We describe a series of 11 patients with the diagnosis of ICU acquired weakness. Neurophysiology plays an essential role in the diagnosis of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
131
0
17

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(153 citation statements)
references
References 28 publications
2
131
0
17
Order By: Relevance
“…With interest we read the article by Cabañes-Martínez et al about 12 patients with COVID-19 and a negative history for neuromuscular disorders (NMDs), who developed muscle weakness and respiratory failure during hospitalization on the intensive care unit (ICU) for complications of the viral infection ( Cabañes-Martínez et al, 2020 ). The authors found that 11 of these patients had critical ill neuropathy (CIN) or critical ill myopathy (CIM) ( Cabañes-Martínez et al, 2020 ).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…With interest we read the article by Cabañes-Martínez et al about 12 patients with COVID-19 and a negative history for neuromuscular disorders (NMDs), who developed muscle weakness and respiratory failure during hospitalization on the intensive care unit (ICU) for complications of the viral infection ( Cabañes-Martínez et al, 2020 ). The authors found that 11 of these patients had critical ill neuropathy (CIN) or critical ill myopathy (CIM) ( Cabañes-Martínez et al, 2020 ).…”
mentioning
confidence: 99%
“…With interest we read the article by Cabañes-Martínez et al about 12 patients with COVID-19 and a negative history for neuromuscular disorders (NMDs), who developed muscle weakness and respiratory failure during hospitalization on the intensive care unit (ICU) for complications of the viral infection ( Cabañes-Martínez et al, 2020 ). The authors found that 11 of these patients had critical ill neuropathy (CIN) or critical ill myopathy (CIM) ( Cabañes-Martínez et al, 2020 ). It was concluded that the prevalence of CIN and CIM will increase with the increasing number of COVID-19 patients requiring ICU treatment and that nerve conduction studies (NCSs) and electromyography (EMG) will play crucial roles in the work-up of neuro-COVID ( Cabañes-Martínez et al, 2020 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations